What is nature? – ziran in early Daoist thinking. Issue 3 (2nd July 2016) - Liu, Jing
ABSTRACT: The question of the relation between humans and nature lies at the foundation of any philosophy. With the daily worsening environmental crisis, we are forced to face this ancient question again. Yet when we put it into the form of 'humans and nature', a metaphysics is already implied and the problem of nature has not yet been questioned. At this moment, the very question that needs to be put forward is, 'What is nature'? The question of nature will be interrogated through a comparative view in this essay. First, I argue the modern understanding of nature lies at the root of today's environmental problems. Then, I go back to early Daoism to explore Daoist thinking on ziran (usually translated as 'nature'). The meaning of ' dao emulates ziran ' is brought to light through a detailed interpretation of the ziran of dao and things. Ziran penetrates the dao, the heavenly, the earthly and the human. It is with the understanding of ziran that the nature of humans and all things are illuminated. Heidegger's thinking on nature in connection with Daoism is briefly examined together with some other significant environmental philosophies.